DECISION-MAKING TO IMPROVE SHALLOW RESERVOIR PRODUCTION WITH SAND PROBLEMS IN MHK AREA, PT XYZ - Devianty C Allagan, Riska
Various sand control technologies have been tried in the MHK field to overcome the sand problem in shallow reservoirs, but the success rate is still low. This is caused by the determination of technology that is not precise without considering reservoir conditions and well completion. Therefore, that a lot of potential loss of production opportunities (LPO) occurs in shallow reservoirs that have sand problems due to the lack of methods that are in accordance with the characters in the MHK field.